Development of PID current control for DC motor using arduino - Ab Ghani, Mohd Khairul Akli (2014)
Power electronic systems have been widely used in varieties of domestic applications and industrial sector due to its reliability, simple construction and low weight. Therefore, this project is to design and to develop of PID Current Control that could be applied for the DC motor. The control technique was called as current control technique by comparing the output current with the reference current. Thus, the PID controller will force the output current to follow the reference current by creating the pulse with modulation (PWM) signals. The PID Controller was developed and simulated by using MATLAB/Simulink software and then implemented to the hardware by using Arduino microcontroller board as a digital signal processing system. The final observation from this project is by using Arduino Uno board, the current of DC motor can control but in small scale. This is due to the current sensor that used had range in small scale reading. Lastly, the result of the performance for this controller was explained in this report by observed in three condition; simulation, open loop control and closed loop control.